PELATIHAN DAN PENDAMPINGAN PENYUSUNAN RENCANA PEMBELAJARAN KURIKULUM 2013 BAGI GURU PAUD - Asyruni Multahada (Jurnal Pengabdian Kepada Masyarakat, 2022)
This community service activity (PKM) aims to improve the understanding of the 2013 curriculum lesson plans for PAUD teachers in Sambas Regency. The method used in this community service activity is Participatory Action Research (PAR). This activity was attended by 12 PAUD institutions consisting of 10 KB institutions and 2 TK institutions with a total of 15 participants. The stages in preparing the 2013 Curriculum lesson plan consist of: 1) Preparation of the Annual Programme and Education Calendar, 2) Determining learning themes and Semester Programme, and 3) Developing RPPM and RPPH. After the 2013 curriculum mentoring programme for early childhood education teachers in Sambas Regency, there were fundamental changes in the participants, including: 1) participants' knowledge about the preparation of 2013 curriculum lesson plans is increasing; 2) able to apply the 2013 curriculum innovatively and creatively; 3) a change in the early childhood education curriculum paradigm which can then improve the ability of the potential and development of early childhood in PAUD institutions in Sambas Regency.